PENGEMBANGAN MEDIA E- (PHYTOPEDIA) BERBASIS MODEL PROJECT KOMPLIT DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SIWA SEKOLAH DASAR PEMBELAJARAN IPAS - Anindya Nahda Syifa Pramesti, Atha; Nur Kumala, Farida; Dwi Yasa, Arnelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of critical thinking skills among fourth-grade elementary school students in IPAS learning, particularly on the topic of photosynthesis, is caused by teacher-centered instruction and the use of conventional, less interactive learning media. This study aims to develop E-Phytopedia media based on the Project Komplit model and to examine its feasibility, practicality, and effectiveness in improving students’ critical thinking skills. The research employed a Research and Development (R&D) method using the 4-D model (Define, Design, Develop). The research instruments included expert validation sheets, teacher and student response questionnaires, and a critical thinking skills test. The results showed that the E-Phytopedia media was categorized as very feasible, with validation percentages of 95% from media experts, 88% from subject matter experts, and 82% from language experts. In addition, the media was considered very practical based on teacher responses (92%) and student responses (90%). The effectiveness test using an Independent Samples t-Test indicated a significant difference between the experimental class and the control class (Sig. < 0.05), with the experimental class obtaining a higher mean posttest score. Therefore, E-Phytopedia media is effective in improving students’ critical thinking skills.